Regional thalamic MRI as a marker of widespread cortical pathology and progressive frontotemporal involvement in amyotrophic lateral sclerosis - Tu, S; Menke, RAL; Talbot, K; Kiernan, MC; Turner, MR (BMJ Publishing Group, 2018)
Background The thalamus is a major neural hub, with selective connections to virtually all cortical regions of the brain. The multisystem neurodegenerative syndrome amyotrophic lateral sclerosis (ALS) has pathogenic overlap with frontotemporal dementia, and objective in vivo markers of extra-motor pathological spread are lacking. To better consider the role of the thalamus in neurodegeneration, the present study assessed the integrity of the thalamus and its connectivity to major cortical regions of the brain in a longitudinal manner. Methods Diffusion-based MRI tractography was used to parcellate the thalamus into distinct regions based on structural thalamo-cortical connectivity in 20 patients with ALS, half of whom were scanned at two time points, and 31 matched controls scanned on a single occasion. Results At baseline, widespread diffusivity alterations in motor- and extramotor-associated thalamic parcellations were detectable. Longitudinal decline selectively affected thalamic regions associated with frontal and temporal lobe connectivity. Diffusivity measures were significantly correlated with clinical measures of disease burden. Progression of functional disability, as indicated by change on the ALS functional rating scale, was associated with longitudinal change in mean diffusivity of the right frontal lobe thalamic parcellation (r=0.59, p=0.05). Conclusions Regional thalamic connectivity changes mirror the progressive frontotemporal cortical involvement associated with the motor functional decline in ALS. Longitudinal MRI thalamic parcellation has potential as a non-invasive surrogate marker of cortical dysfunction in ALS.